Subcutaneous phaeohyphomycosis caused by Phaeoacremonium parasiticum in a renal transplant patient - Marques, Silvio Alencar [UNESP]; Camargo, R. M. P.; Summerbell, R. C.; De Hoog, G. S.; Ishioka, P.; Chambo-Cordaro, L. M.; Marques, Mariângela Esther Alencar [UNESP] (Taylor & Francis Ltd, 2006)
A 49-year-old renally transplanted man, under a five-year course of immunosuppressive therapy with prednisone and cyclosporine A, experienced a subcutaneous phaeohyphomycosis caused by Phaeoacremonium parasiticum. The clinical presentation consisted of impressive, large, inflammatory and draining cystic tumors on the left foot that had been present for one year. A significant improvement was obtained with itraconazole plus intralesional injection with amphotericin B. Drug interaction was observed between itraconazole and cyclosporine A causing a severe hypertensive crisis and requiring a temporary sharp reduction in cyclosporine administration. Subcutaneous phaeohyphomycosis caused by P. parasiticum is uncommon among major organ transplant patients but several cases have previously been published and some patterns are emerging, e. g., limbs are generally involved but no known traumatic event has preceded lesion development. The identification of the case isolate was confirmed using a recently published online system based in part on beta-tubulin sequence comparison.
Keywords: subcutaneous phaeohyphomycosis; Phaeoacremonium parasiticum; kidney transplant; immunosuppressive therapy